2022
DOI: 10.1155/2022/9253634
|View full text |Cite
|
Sign up to set email alerts
|

Research on Open Innovation Intelligent Decision-Making of Cross-Border E-Commerce Based on Federated Learning

Abstract: Product development and innovation is the key issue for cross-border e-commerce operation. It is of great importance to build an intelligent open innovation system and maximize its proximity to market demand with the internationalization and digital advantages of cross-border e-commerce. Cross border e-commerce data is widely distributed among each node enterprise in the supply chain. But the enterprises will not share private data for intelligent learning for the sake of data security, which has become a diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…To this end, FRSs can allow different data sources to collaborate in order to provide personalized recommendations to customers. A literature review on the application of FRSs in E-commerce revealed the various advantages [179][180][181]. First, FRSs can help reduce the cost of data access and storage.…”
Section: E-commercementioning
confidence: 99%
“…To this end, FRSs can allow different data sources to collaborate in order to provide personalized recommendations to customers. A literature review on the application of FRSs in E-commerce revealed the various advantages [179][180][181]. First, FRSs can help reduce the cost of data access and storage.…”
Section: E-commercementioning
confidence: 99%